The responses of low-latitude D region ionosphere to solar flares during 2014 - Tan, Le Minh (Vietnam Journal of Earth Sciences, 2016)
93 solar flare events were recorded by using the Very Low Frequency (VLF) wave, 19.8 kHz from North West Cape (NWC), Australia to Tay Nguyen University (12.65°N, 108.02°E), Vietnam during 2014 to study the responses of the low-latitude D region ionosphere to solar flares. The observed VLF amplitude and phase perturbations are used as the input parameters for the simulated LWPC (Long-Wavelength Propagation Capability) program, using Wait’s model of lower ionosphere, to estimate the Wait’s parameters, the reference height (h’), and the electron density gradient (b). The results reveal that when the X-ray irradiance (l < 1 nm) increases, the b increases from 0.31 to 0.53 km-1, while h’ decreases from 72.8 to 60.9 km. The values of h’ observed at low latitudes are higher, but the values of b are lower than those observed at middle latitudes during perturbed conditions. The representation of the electron density changes with altitude and time supports to deeply understand the behavior of the D-region ionosphere during solar flares. References Basak, T. & Chakrabarti, S. K., 2013: Effective recombination coefficient and solar zenith angle effects on low-latitude D-region ionosphere evaluated from VLF signal amplitude and its time delay during X-ray solar flares, Astrophys. Space Sci., 348, 315-326. Collis, P. N., Hargreaves, J. K., White, G. P, 1996: A localised co-rotating auroral absorption event observed near noon using imaging riometer and EISCAT, Ann. Geophys., 14, 1305-1316. Cummer, S. A., Inan, U. S. and Bell, T. F., 1998: Ionospheric D region remote sensing using VLF radio atmospherics, Radio Sci., 33(6), 1781-1792. Dahlgren, H., Sundberg T., Andrew B. C., Koen E., and Meyer S., 2011: Solar flares detected by the new narrowband VLF receiver at SANAE IV, S Afr. J. Sci., 107, 1-8. Ferguson, J. A., 1995: Ionospheric model validation at VLF and LF, Radio Sci., 30(3), 775-782. Grubor, D., Šulíc D. and Žigman V., 2008: Classiﬁcation of X-ray solar ﬂares regarding their effects on the lower ionosphere electron density proﬁle, Ann. Geophys., 26, 1731-1740. Gustafsson, M., 2011: Detection of solar flare induced ionospheric perturbations on narrowband VLF transmissions, Thesis of Master, KTH School of Electrical Engineering, Stockholm, Sweden. Hargreaves, J. K., 1992: The Solar - Terrestrial environment. Cambridge Univesity Press, pp. 420. Kumar, A., 2007: Amplitude and phase study of sub-ionospheric VLF radio signal receiver at Suva, Master thesis, The University of the South Pacific, Suva, Fiji. Mitra, A. P. & Rowe, J. N., 1972: Ionospheric effects of solar flares. VI. Changes in D-region ion chemistry during solar flares, J. Atmos. Terr. Phys., 34 (5), 795-806. Mitra, A. P., 1974: Ionospheric Effects of Solar Flares. D. Reidel, Dordrecht, Holland. Rogers, J. C., Peden I. C., 1975: The VLF complex permittivity of deep Antarctic ice measured in situ, Radio Sci., 10, 763-771. Scherrer, D., Mitchell, R., Huynh, T., Lord, W., and Lord, M., 2009: SuperSID manual - Space weather monitor, Stanford University Solar Center. Tan M. L, Thu N. N., Ha T. Q., 2014: Observation of the effects of solar flares on the NWC signal using the new VLF receiver at Tay Nguyen University, Sun & Geosphere, 8(1), 27-31. Thomson, N. R., & McRae, W. M., 2009: Nighttime ionospheric D region: Equatorial and nonequatorial, J. Geophys. Res.,114, A08305. Thomson, N. R., Clilverd, M. A., 2001: Solar ’are induced ionospheric D-region enhancements from VLF amplitude observations, J. Atmos. Terr. Phys., 63, 1729-1737. Thomson, N.R., Clilverd, M.A., McRae, W.M., 2007: Nighttime ionospheric D region parameters from VLF amplitude and phase, J. Geophys. Res., 112. Turunen, E., Matveinen, H. and Ranta, H., 1992: Sodankyla Ion Chemistry (SIC) Model, Sodankyla Geophysical Observatory, Rept. 49, Sodankyla, Finland. Wait, J. R. and Spies K. P., 1964: Characteristics of the Earth-ionosphere waveguide for VLF radio waves. NBS Tech. Not., pp. 300. World Meteorological Organization (WMO), 2009: The Potential Role of WMO in Space Weather. Accessed 2009. Žigman, V., Grubor D.and Šulíc D., 2007: D-region electron density evaluated from VLF amplitude time delay during X-ray solar ﬂares, J. Atmos. Sol. Terr Phys., 69 (7), 775-792. http://www.ultramsk.com/ http://legacy-www.swpc.noaa.gov/info/Radio.pdf